In vitro and in vivo susceptibility of the honey bee bacterial pathogen Paenibacillus larvae subsp larvae to the antibiotic tylosin - Alippi, Adriana Mónica (2005)
The minimal inhibitory concentrations (MICs) of tylosin were determined to 67 strains of Paenibacillus larvae subsp. larvae, the causal agent of American Foulbrood (AFB) disease, from different geographical origins. MIC values obtained ranged from 0.0078 to 0.5 microg/ml. These very low values imply that no resistance to tylosin was found in any isolate of the Foulbrood pathogen. The measurement of diseased larvae with AFB-clinical symptoms in three different field studies demonstrated that tylosin treatment could be effective in vivo. No negative effects in colonies were noted at any dosage rates or forms of application. These studies demonstrate that tylosin, as tartrate, can be used to treat AFB in honeybee colonies.